2013
DOI: 10.1111/hiv.12056
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, feasibility and costs of universal offer of rapid point of care testing for HIV in an acute admissions unit: results of the RAPID project

Abstract: ObjectivesUK guidance recommends that acute medical admissions are offered an HIV test. Our aim was to determine whether a dedicated staff member using a multimedia tool, a model found effective in the USA, is an acceptable, feasible, and cost-effective model when translated to a UK setting. MethodsOver 4 months in 2010, a health advisor (HA) approached 19-65-year-olds at a central London acute medical admissions unit and offered a rapid HIV point of care test (POCT) with the aid of an educational video. Feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…There were two educational interventions targeting patients; one for pregnant women , which resulted in an increase in testing coverage (from 87 to 92%) after provision of a patient information leaflet and one for patients admitted to a hospital inpatient unit, where there was a decline in test offer (from 8 to 0%) . All four communication technology studies were directed to patients, with two providing videos on HIV testing , one utilizing text messages to recall MSM for testing and one using online platforms for partner notification . The only study measuring intervention impact reported an increase in the re‐testing rate among MSM who were actively recalled (from 19 to 44%) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were two educational interventions targeting patients; one for pregnant women , which resulted in an increase in testing coverage (from 87 to 92%) after provision of a patient information leaflet and one for patients admitted to a hospital inpatient unit, where there was a decline in test offer (from 8 to 0%) . All four communication technology studies were directed to patients, with two providing videos on HIV testing , one utilizing text messages to recall MSM for testing and one using online platforms for partner notification . The only study measuring intervention impact reported an increase in the re‐testing rate among MSM who were actively recalled (from 19 to 44%) .…”
Section: Resultsmentioning
confidence: 99%
“…Novel HIV testing technologies were employed by 40 studies in a wide range of clinical settings to increase testing coverage; the majority utilized rapid testing (n = 36) [18,19,22,24,25,34,36,45,46,[48][49][50]56,57,59,65,75,77,81,83,85,88,89,[99][100][101]107,113,117,129,132,134,137,139,141] while four utilized self-sampling (n = 3) [44,52,102] and self-testing strategies (n = 1) [108]. Two of the four self-sampling studies used oral fluid sampling while the self-test required a blood sample.…”
Section: Testing Provision Strategiesmentioning
confidence: 99%
“…Availability of counselling or a pathway to refer discharged patients for outside counselling and testing should be routinely provided in all emergency departments in order to detect HIV infection early . If available, an acute admissions unit could provide timely in‐house testing without the use of extra resources , but a recent UK audit showed inadequate testing even after introduction of simplified guidelines, particularly in patients with shorter hospital stays and in patients not seen by an infectious disease specialist .…”
Section: Discussionmentioning
confidence: 99%
“…Patient attitudes about and willingness to go undergo HIV testing vary among populations, settings, and testing strategies (Burns et al, 2013; Christopoulos et al, 2012; Cunningham et al, 2009; Goetz et al, 2008; Jain et al, 2008; Lin et al, 2014; Merchant et al, 2008). The majority of studies reporting on these attitudes and behaviors use cross-sectional designs that do not account for the serial nature of how individual patients interact with health-care systems.…”
Section: Discussionmentioning
confidence: 99%
“…Variable rates of testing across different care settings, including the Emergency Department (ED), inpatient, and outpatient settings, suggest that some patients may be more likely to test in one setting over another (Burns et al, 2013; Cunningham et al, 2009; Goetz et al, 2008; Jain et al, 2008; Lin et al, 2014; Merchant et al, 2008). Health-care systems have serial encounters with the same patients across these care settings; however, few studies have examined the role of reoffering HIV testing after a patient declines.…”
Section: Introductionmentioning
confidence: 99%